Structural Market Distortions in Indonesia's Aviation Industry: Evidence of Monopolistic Practices, Price Discrimination, and Cartel Activities by the Lion Air Group - Seselia Ongso; Sugeng Santoso PN (Eduvest - Journal of Universal Studies, 2026)
There is an indication of market dominance through a cooperation agreement that has the potential to limit the access of other business actors and cause discriminatory treatment. One of the cases of monopoly practices is market control through a cooperation agreement by Lion Air Group in ICC Decision Number 07/ICC-I/2020 and Cassation Decision Number 1811K/Pdt.Sus-ICC/2022. The research method employed is doctrinal legal research using a library research and statute approach, by examining legal regulations on monopoly, discrimination, and cartel practices, which are then analyzed alongside material facts and judicial ratio decidendi. The results of the study show that the monopoly practice in ICC Decision Number 07/ICC-I/2020 is reflected in the granting of exclusive rights to use cargo capacity to PT Lion Express which has an impact on limited access for other business actors and fulfills the elements of violation of Article 19 letter d of Law No.5/1999. In addition, indications of cartel pricing and practices were also found through the uniformity of flight fare policies by the Lion Air Group in Cassation Decision Number 1811K/Pdt.Sus-KPPU/2022. Although, the evidence of alleged cartel practices was not met, the Panel of Judges still affirmed the existence of cartel violations as intended in Article 5 of Law No. 5/1999. Therefore, this study emphasizes that monopoly practices can trigger unfair business competition, so strict supervision by ICC is needed to ensure the achievement of healthy, fair, and efficient business competition in the aviation industry.